National symposium on problems of presymptomatic testing for Huntington's disease, Cardiff. Issue 1 (March 1990) - Tyler, A; Morris, M
Abstract : Presymptomatic testing for Huntington's disease has given rise to several ethical problems relating to such issues as confidentiality, the privacy of the individual, the testing of minors and informed consent in connection with blood sample donation. A multidisciplinary conference of staff from genetic centres involved with presymptomatic testing was organised in Cardiff to discuss these and other problems. Recommendations on good practice are described under four headings: pre- and post-test counselling; confidentiality in relation to test results; collection and storage of DNA, and criteria for testing.